2022
DOI: 10.1021/acssuschemeng.1c08629
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Power Output of a Cement-Based Triboelectric Nanogenerator by Enhancing Dielectric Polarization with Highly Dispersed Carbon Black Nanoparticles toward Large-Scale Energy Harvesting from Human Footsteps

Abstract: A strategy to enhance the energy conversion performance of a cement-based triboelectric nanogenerator (TENG) has been proposed for large-scale energy harvesting from human footsteps. A cement-carbon black (CB) composite is fabricated by incorporating CB nanoparticles with a hydroxyethyl cellulose (HEC) admixture and used as a triboelectric material for TENG. The fabricated cement-CB@HEC TENG exhibits a 13fold enhancement of the electrical output with the highest power density of 2.38 W/m 2 . The tremendous imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Many strategies have been proposed to enhance the TENG performance, which mainly aim to intensify triboelectric charges on triboelectric materials. , Besides the selection of tribo-materials, modifying the surface/internal structure with nanostructure to enhance friction area and improving charge retention by tuning dielectric constant of tribo-materials , are the main approaches for boosting power density of TENG. In the latter case, filling the triboelectric material with a conductive material such as metal, metal oxide, and conductive carbon nanoparticles is one of the most effective approaches to enhance charge trapping ability ,, from an improvement in the dielectric constant of triboelectric materials. In addition, the diversity of filler material choices, the ease of fabrication, and the robustness of the triboelectric film are the key benefits offered by this approach whereas the surface modification ones may require a sophisticated fabrication process and the surface nanostructures could be damaged or worn out during contact/sliding TENG operations.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have been proposed to enhance the TENG performance, which mainly aim to intensify triboelectric charges on triboelectric materials. , Besides the selection of tribo-materials, modifying the surface/internal structure with nanostructure to enhance friction area and improving charge retention by tuning dielectric constant of tribo-materials , are the main approaches for boosting power density of TENG. In the latter case, filling the triboelectric material with a conductive material such as metal, metal oxide, and conductive carbon nanoparticles is one of the most effective approaches to enhance charge trapping ability ,, from an improvement in the dielectric constant of triboelectric materials. In addition, the diversity of filler material choices, the ease of fabrication, and the robustness of the triboelectric film are the key benefits offered by this approach whereas the surface modification ones may require a sophisticated fabrication process and the surface nanostructures could be damaged or worn out during contact/sliding TENG operations.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, carbon black (CB) is often used as a conductive filler due to its high conductivity, availability, and low specific gravity . In addition, CB can significantly improve the dielectric constant of polymer substrate. , The increase of the dielectric constant of friction layers can remarkably improve the charge storage ability of friction layers and decrease the output impedance of TENG to increase its output performance. , Li et al found that introducing CB into the PS fiber membranes could boost the charge transfer rate and storage depth of triboelectric charges, which significantly enhanced the output of TENG.…”
Section: Introductionmentioning
confidence: 99%
“…Cement is a fundamental construction material that generally faces a lot of mechanical energy such as human walking, movement of vehicles, and vibration from the environment, thus this makes it an attractive candidate material for the development of cement-based triboelectric nanogenerators (C-TENGs). In previous works, the optimization of electricity generation performance in C-TENGs was conducted through the doping of high-dielectric constant materials, such as carbon black [1] and TiO2 nanoparticles [2].…”
Section: Introductionmentioning
confidence: 99%